Framing discomfort on YouTube: Narratives of non-binary dysphoria - Letizia Paglialunga (Revista Alicantina de Estudios Ingleses)
In Western thinking, the binary gender system has long held a central position, often side-lining identities that exist beyond this binary framework. This facet of gender discourse frequently leads to the omission of non-binary individuals from discourses not only of gender, but more broadly of societal concern. As a result, it is not unusual for these individuals to experience discomfort, both in respect of their gender identity and in relation to societal expectations, often leading to gender dysphoria. It is no chance, in light of the above, that clinical definitions and comprehension of gender dysphoria predominantly center on a binary understanding of gender, even though the experience of gender dysphoria extends beyond this binary framework. Over the past decade, social-media platforms have emerged as dynamic arenas where non-binary individuals can openly express their gender identities. In this context, social-media holds considerable influence as a potent tool (Angouri, 2021) for the construction and portrayal of non-binary identities online. Within this discourse, the articulation of discomfort with one’s own physical appearance seems to be a recurring theme. This study explores the articulation of emotional discomfort among non-binary YouTubers, in relation to their gender experience. It employs a methodology relying on Corpus Assisted Discourse Studies (Gillings et al., 2023), using the Sketch Engine software (Kilgarrif et al., 2014), to identify distinctive lexical patterns that characterize the expression of discomfort and dysphoria. The dataset includes YouTube videos from five channels owned by non-binary YouTubers, which could be considered, by virtue of their content and stated purpose, as explicit non-binary communicative gender performances. The paper primarily investigates how discourse surrounding suffering and discomfort contributes to the portrayal of non-binary identities in online spaces, and seeks to observe whether the expression of this discomfort can be construed as a means of seeking validation for these identities within the social-media domain.